2007
DOI: 10.1111/j.1365-2885.2007.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and oral bioavailability of amoxicillin and clavulanic acid in pigs

Abstract: The pharmacokinetic properties of amoxicillin and clavulanic acid were studied in healthy, fasted pigs after single intravenous (i.v.) and oral (p.o.) dosage of 20 mg/kg of amoxicillin and 5 mg/kg of clavulanic acid. The plasma concentrations of the drugs were determined by validated high-performance liquid chromatographic methods and the pharmacokinetic parameters were calculated by compartmental and noncompartmental analyses. After i.v. administration of the two drugs, plasma concentration-time curves were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
(77 reference statements)
4
31
2
Order By: Relevance
“…The V z of AMX calculated here was relatively higher than those reported in dogs (0.312 L/kg; Kung & Wanner, ) and pigs (0.55 L/kg; Agerso & Friis, ). The present V ss values of AMX and CLV were also wider than those, with the same values of 0.34 L/kg, reported in pigs after intravenous administration of the combination of AMX‐CLV (Reyns et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The V z of AMX calculated here was relatively higher than those reported in dogs (0.312 L/kg; Kung & Wanner, ) and pigs (0.55 L/kg; Agerso & Friis, ). The present V ss values of AMX and CLV were also wider than those, with the same values of 0.34 L/kg, reported in pigs after intravenous administration of the combination of AMX‐CLV (Reyns et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…The terminal half‐life ( t 1/2λz ) was determined as 1.26 and 0.69 hr for AMX and CLV, respectively (Tables and ), and the total body clearance was estimated as 0.453 and 0.921 L hr −1 kg −1 (Tables and ), respectively. The clearance of AMX reported here was close to that in pigs ranging from 0.37 to 0.59 L hr −1 kg −1 (Agerso & Friis, ; Reyns et al, ); however, a relatively slower elimination was reported in dogs with a steady‐state rate of clearance of 0.204 L hr −1 kg −1 (Kung & Wanner, ). After oral combination administration, the t 1/2λz of AMX was estimated to be 1.25 hr (Table ), which was very close to that value (1.26 hr) previously reported in cats after oral dosing of AMX alone (Chicoine et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Atomic coordinates are taken from the code 1AO6 [82] of the Protein Data Bank. concentration levels approximately 1 h after oral administration, with similar time-concentration profiles [75], low levels of serum protein binding with approximately 70% of the drug remaining free in serum (as described in Vademecum) and a mean bioavailability of 22.8% [76]. A great variability in the clearance of both AX and CLV has been found in critically ill patients treated with AX-CLV [77].…”
Section: Candidate Proteins For Drug Conjugate Formationmentioning
confidence: 89%
“…, 2009). Oral bioavailability and pharmacokinetic behavior of the combination was investigated in pigs (Reyns et al. , 2007), goats (Carceles et al.…”
Section: Mean ± Se Pharmacokinetic Parameters Of Amoxicillin After Smentioning
confidence: 99%